Survival tactics of Bacillus licheniformis KNP under hexavalent chromium stress: a study of detoxification and chemotactic responses - Garg, Akansha; Ali, Mushtaq; Ahmad, Aiman; Chauhan, Prerna; Kumar, Ashish; Mishra, Rupali; Dubey, Vimal Kumar; Srivastava, Alok; Garg, Sanjay Kumar; Arora, Pankaj Kumar (Frontiers in Microbiology, 2025)
Hexavalent chromium [Cr(VI)] pollution is a serious environmental issue because it is highly toxic and persistent. We aimed to investigate the growth, Cr(VI) reducing capacity, and chemotaxis of Bacillus licheniformis strain KNP under the stress of Cr(VI) in the form of K2Cr2O7 (250–1,000 ppm). Bacterial growth decreased as Cr(VI) concentration increased, with a maximum at 250 ppm K2Cr2O7 and strong inhibition at 1,000 ppm K2Cr2O7. Significantly, strain KNP completely reduced Cr(VI) in the form of 500 ppm K2Cr2O7 within 48 h. Fourier Transform Infrared spectroscopy (FTIR) showed biochemical changes of functional groups present on bacterial cell wall due to interaction with chromium. A scanning electron microscope (SEM) and energy dispersive X-ray spectroscopy (EDX) analysis confirmed the accumulation of Cr on the surface of bacteria with morphological changes. Strain KNP also showed negative chemotaxis away from Cr(VI) and positive chemotaxis toward glucose, as indicated by drop plate and chemical plug assays. Genomic analysis revealed major chemotaxis-related genes that play a role in Cr(VI) sensing and avoidance, indicating a complex survival strategy. These results indicated that B. licheniformis strain KNP is a good candidate for bioremediation purposes, providing an effective combination of Cr(VI) detoxification and tactical bacterial migration in polluted environments.